2015
DOI: 10.4238/2015.july.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism in sex hormone metabolism and prostate cancer risk

Abstract: ABSTRACT. We compared single-nucleotide polymorphisms for point mutations in cytochrome P450 genes, including cytochrome P450c17α (CYP17), cytochrome P450 aromatase (CYP19), steroid-5-a-reductase (SRD5A2), and prostate-specific antigen (PSA) involved in androgen and estrogen production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Nevertheless, in a study performed among Turkish men, an apparent elevation in BPH risk was found in those with the T allele of SRD5A2 rs9282858 polymorphism, but the rs523349 polymorphism was detected to have no significant influence on the disease risk (Izmirli et al, 2011 ). Similarly, another study by Ersekerci et al among Turkish men as well, showed no significant difference in genotype or allele distribution of rs523349 polymorphism between case and control groups (Ersekerci et al, 2015 ). A study by Li et al found no apparent linkage between the two SNPs and BPH in a Japanese population either (Li et al, 2003 ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, in a study performed among Turkish men, an apparent elevation in BPH risk was found in those with the T allele of SRD5A2 rs9282858 polymorphism, but the rs523349 polymorphism was detected to have no significant influence on the disease risk (Izmirli et al, 2011 ). Similarly, another study by Ersekerci et al among Turkish men as well, showed no significant difference in genotype or allele distribution of rs523349 polymorphism between case and control groups (Ersekerci et al, 2015 ). A study by Li et al found no apparent linkage between the two SNPs and BPH in a Japanese population either (Li et al, 2003 ).…”
Section: Discussionmentioning
confidence: 87%
“…Among the remaining 58 articles, 27 had no control group, 14 were not associated with SRD5A2 polymorphisms, 5 were drug dose researches, 2 were duplicate reports, and another 2 contained insufficient data. As a result, 1,865 cases and 1,424 controls were included in the present meta-analysis (Li et al, 2003 ; Giwercman et al, 2005 ; Salam et al, 2005 ; Das et al, 2008 ; Rajender et al, 2009 ; Izmirli et al, 2011 ; Choubey et al, 2015 ; Ersekerci et al, 2015 ). Characteristics of the included studies are provided in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…, which is through CYP19A1 SNPs, especially through increasing the genotype TT of the rs700518 gene expression, which causes the metabolism level of estrogen to increase, leading to a reduction in the T/E ratio; this triggers IR, raises blood glucose levels, and promotes hyperplasia of prostate gland acinar cells and stromal cells in the prostate tissue, leading to the occurrence of clinical BPH and MetS. In contrast, BPH can lead to a systemic metabolic disorder, which can lead to IR, resulting in MetS (Crawford et al ., ; Balistreri et al ., ; Ersekerci et al ., ; Cornu et al ., ). Moreover, through IR, MetS and BPH interact and progress clinically.…”
Section: Discussionmentioning
confidence: 99%
“…A study recently reported on two populations of African ancestry failed to show any association between rs60271534 and prostate cancer risk [17]. Another SNP 1531 C > T was investigated in the Turkish prostate cancer patients, but no significant association was observed [102]. Lévesque et al [103] reported a study in which results obtained in Caucasians and Taiwanese were compared.…”
Section: Variations In Cyp19a1 Gene and Prostate Cancermentioning
confidence: 99%